Relevant factors for neurologists to define effectiveness of migraine preventive drugs and take decisions on treatment. My‐LIFE European Delphi survey. (13th July 2021) - Pozo‐Rosich, Patricia; Gil‐Gouveia, Raquel; Donnet, Anne; Poole, Anne‐Christine; Gendolla, Astrid; Afridi, Shazia; Sanchez‐De la Rosa, Rainel; Terwindt, Gisela M.; Tassorelli, Cristina
Abstract: Background: Clinical guidelines agree that preventive treatment should be considered in patients with uncontrolled migraine despite acute medications or patients with ≥4 migraine days per month. However, the criteria to define the effectiveness of treatment and the factors that inform the decision to (dis)continue it are not clearly defined in clinical practice. Methods: Overall, 148 healthcare practitioners from five European countries completed a two‐wave questionnaire. The Steering Committee defined a simulated set of 108 migraine patient profiles based on the combination of five factors (frequency of the attacks, intensity of the attacks, use of acute migraine medications, patient perception and presence/absence of tolerable side effects). These profiles were used in a Delphi survey among European neurologists to identify the criteria that should be used to decide treatment response and continuation using a conjoint analysis approach. Results: Consensus was reached for 82/108 (76%) of profiles regarding treatment response, and for 86/108 (80%) regarding treatment continuation. Multivariable logistic regression analysis showed that a ≥50% reduction in the use of acute migraine medications and positive patient's perception of treatment were the most important factors that lead to the decision of continuing (combined factors, OR = 18.3, 95% CI 13.4–25.05). Conclusions: This survey identifies two relevant outcome measures: one objective (use of acute migraine treatment medications) and one subjective (positive patient perception) that guide the clinician decision to continue preventive treatment in migraine patients. Significance: In clinical practice, criteria to define the effectiveness of migraine preventive treatment and factors that guide treatment stop or continuation are not clearly defined. In this simulated clinical setting study, a reduction in the use of acute migraine medications was the factor associated with preventive treatment effectiveness definition. This study also revealed that factors strongly associated with the decision of treatment continuation in real life are the acute migraine medications use and a positive patient's perception of treatment effectiveness.